Eclectic Maharah Kalam and Kitabah: Solution or Obstacle? in Arabic Language Learning for MTs Student - Irawan, Diazzahra Dinda; Fahmi, Ari Khairurrijal; Nadia, Ahsanu (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
The application of the eclectic method in improving maharah kalam and kitabah of students in class 8.3 MTs Muhammadiyah 1 Depok, which low student interest in mastering Arabic speaking and writing skills still becomes a challenge. The eclectic method, which integrates various learning strategies and media, is expected to be a creative solution to improve the quality of learning. Although many teachers have implemented this method, a deep theoretical understanding is often lacking, making it a challenge in its implementation. A qualitative approach with a case study design was used and the data were collected through observation, questionnaires to students, and interviews with teachers. The result of the analysis showed that the application of eclectic methods in an appropriate and directed manner can significantly improve students’ skill in maharah kalam and maharah kitabah. This article confirmed the importance of a deep understanding of the eclectic method to optimize the Arabic language learning process. The contribution of this research not only focuses on evaluating the effectiveness of eclectic methods, but also provides recommendations for the development of more effective learning strategies in the classroom, so as to improve students speaking and writing skills in a sustainable manner. Thus, this research has the potential to have a positive impact on Arabic language teaching at the MTs level, as well as being a reference for the development of more innovative learning methods.